EVALUASI KESESUAIAN PERAIRAN UNTUK BUDIDAYA IKAN BETUTU Oxyeleotris marmorata (BLEEKER, 1852) DI DESA RANTAU JAYA MAKMUR SUNGAI WAY PEGADUNGAN KECAMATAN PUTRA RUMBIA KABUPATEN LAMPUNG TENGAH - Diantari, Rara; Damai, Abdullah Aman; Pratiwi, Leoni Dian (University of Lampung, 2018)
Way Pegadungan is a tributary of Way Seputih, has a length of 35.31 km and a river width of 50 to 70 meters. Way Pegadungan is very potential for aquaculture but has not been used optimally. This research was held in March - May 2018 using a descriptive quantitative method aimed at assessing the level of suitability of the waters by knowing the physical and chemical parameters for the cultivation of betutu fish. The data used primary data, namely the parameters of water suitability in the form of water quality values, while the secondary data is in the form of research location maps. Water suitability analysis was carried out using matching and scoring methods. The range of data obtained is depth: 6-7 m, brightness: 37,5-55 cm, temperature: 28-29ÂºC, pH: 7-8,21, dissolved oxygen: 4,02-6,73 mg / l, current : 0,14-0,16 m / s, nitrate: 0,16-0,21 mg / l, phosphate: 0,01-0,025 mg / l, ammonia: 0,01-0,065 mg / l, organic matter: 6,7-10,76 mg / l. Sampling stations were 4 stations determined by the global positioning system (GPS). At the first and fourth points get moderately sutableÂ (S2) and at the second and third points get marginal sutable (S3).